2020
DOI: 10.1109/jbhi.2019.2956604
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Cardiac Output and Central Systolic Pressure From Cuff-Pressure and Pulse Wave Velocity

Abstract: Goal: We introduce a novel approach to estimate cardiac output (CO) and central systolic blood pressure (cSBP) from noninvasive measurements of peripheral cuff-pressure and carotid-to-femoral pulse wave velocity (cf-PWV). Methods: The adjustment of a previously validated one-dimensional arterial tree model is achieved via an optimization process. In the optimization loop, compliance and resistance of the generic arterial tree model as well as aortic flow are adjusted so that simulated brachial systolic and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 73 publications
(87 reference statements)
2
30
0
Order By: Relevance
“…The results presented in this study are also compliant with the findings of Bikia et al 49 , who suggested that brachial BP and cfPWV can be used to predict central SBP and CO (RMSE equal to 2.46 mmHg and 0.36 L min −1 , respectively). Following an inverse problem-solving approach, a generalized model of the cardiovascular system was adjusted to quasi-patient-specific standards using measurements of brSBP, brDBP, HR, and cfPWV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results presented in this study are also compliant with the findings of Bikia et al 49 , who suggested that brachial BP and cfPWV can be used to predict central SBP and CO (RMSE equal to 2.46 mmHg and 0.36 L min −1 , respectively). Following an inverse problem-solving approach, a generalized model of the cardiovascular system was adjusted to quasi-patient-specific standards using measurements of brSBP, brDBP, HR, and cfPWV.…”
Section: Discussionsupporting
confidence: 92%
“…Total arterial compliance was chosen within the range of [0.10, 3.80] mL mmHg −1 in order to account for a wide range of different values of arterial tree stiffness 72 , 73 . It should be noted that evidence of nonuniform aortic stiffening was integrated for the elderly and hypertensive virtual subjects, following the methodology described by Bikia et al 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Total peripheral resistance and arterial compliance were altered according to the literature ( Langewouters, 1982 ; Lu and Mukkamala, 2006 ; Segers et al, 2008 ). To simulate older or hypertensive individuals, in some cases, stiffening in the aorta was considered as non-uniform and more pronounced as described in our previous works ( Pagoulatou et al, 2019 ; Bikia et al, 2020a ). For a given set of input parameters, the model provides analytical solutions of the pressure and flow at every arterial segment.…”
Section: Methodsmentioning
confidence: 99%
“…The selected distributions of the input model parameters are summarized in Table 2 . The parameters of arterial distensibility and terminal compliance were altered simultaneously, while nonuniform aortic stiffening was considered for the elderly and hypertensive virtual subjects, following the methodology described in our previous work ( Bikia et al, 2019 ; Pagoulatou et al, 2019 ). Peripheral resistances were modified uniformly in order to achieve the specific value of total peripheral resistance in the selected range.…”
Section: Methodsmentioning
confidence: 99%